Pemanfaatan Video Pembelajaran Pada Google Classroom Untuk Meningkatkan Hasil Belajar Mata Pelajaran Sistem Komputer Di SMK - Yanto, Rudi (Jurnal Vokasi Teknik Informatika, 2022)
Current technology developments have altered the order of human life activities. A touch of technology provides several conveniences in carrying out duties. This is also evident in the educational sector. For education to be integrated, it must undergo a transformational process. Various breakthroughs in curriculum creation, learning innovation, and educational facility and infrastructure fulfillment are required to increase educational quality. Teachers must make learning more inventive so that students may learn effectively in both independent and classroom settings. Initially, in the distance learning process, the teacher just delivered module files or electronic books on the learning platform. However, the learning process has not yielded the best outcomes, necessitating the development of new ways to address these issues. One of the innovations that teachers can do is to design video-based learning media. A learning video has the advantage of being able to present audio (sound) and visuals (images) that describe and explain concepts and procedures for learning material. The purpose of this study was to determine the effect of using learning videos on improving learning outcomes in computer systems subjects in vocational schools. The research method used is a one-group pretest-posttest design, which involves only one experimental class to determine the effect of using learning videos on Google Classroom to improve learning outcomes for computer systems subjects in SMK. According to data analysis results, the utilization of learning videos is highly beneficial in increasing student learning outcomes in computer systems subjects. The percentage increase in student learning outcomes is 9.24%.